Ethanol and ultrasound pre-treatments to improve infrared drying of potato slices - Rojas M.L. (2018)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil) for funding the project n° 2016/18052-5; to the National Council for Scientific and Technological Development (CNPq, Brazil) for funding the project n° 401004/2014-7 and the productivity grant of P.E.D. Augusto (306557/2017-7); and to Cienciactiva for the M.L. Rojas Ph.D. scholarship (CONCYTEC, Peru; Contract 087-2016-FONDECYT), from the “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica”.